DETERMINING THE PERIOD OF ELECTION AFTER POSTPONEMENT CAUSED BY COVID-19: THE CASE OF ETHIOPIA - Shiferaw, zelalem (Jimma University Journal of law, 2022)
Like the case in many States, Covid-19 has disrupted the election process of Ethiopia. It forced the government to postpone the national election which was scheduled for August 29/2020 and bypass the legal requirement of holding the national election every five years. The Constitution of the Federal Democratic Republic of Ethiopia (the FDRE Constitution, hereafter) does not explicitly set out when the election should take place in the event postponing it is necessitated by an emergent situation such as an outbreak of a pandemic. Notwithstanding this Constitutional lacuna, the House of the Federation (HOF), one of the Houses of the Federal Parliament, handled the matter and decided by interpreting the Constitution that the election should be held within 9 months but not later than one year after the control of the pandemic. In this article, I have assessed whether the HOF had the authority to determine the election period.